Pelestarian Ronggiang Pasaman Bersama Grup Ranah Sialang di Nagari Ujung Gading Kecamatan Lembah Melintang Kabupaten Pasaman Barat - Diana Yosmadia; Darmawati Darmawati (FBS Universitas Negeri Padang, 2023)
This research is an effort to preserve Ronggiang Pasaman with the Ranah Sialang group in Lembah Melintang District, Ujung Gading Nagari, West Pasaman Regency. This type of research is qualitative research using descriptive methods. The research instrument was the researcher herself and assisted by supporting instruments such as stationery, flash drives and cameras. The data in this study uses primary data and secondary data. Data collection techniques were carried out by means of literature study, observation, interviews and documentation. The steps to analyze the data are data reduction and data presentation. The results showed that the conservation efforts carried out by researchers were to increase the number of actors in Ujung Gading village, Melintang valley sub-district, West Pasaman district by collaborating with the chairman, dancers from the Ranah Sialang group and the community, the form of collaboration carried out by researchers was socializing related to conservation activities this. Ronggiang Pasaman art already has successors to maintain its existence from traditional arts. It can be proven by the development in terms of the quantity of actors (dancers), in Ronggiang Pasaman Art as many as 10 people, on the other hand, the goal of preservation efforts is so that Ronggiang Pasaman art can continue to develop among young people so that people know that they have a traditional dance that should be proud of and there needs to be an effort to preserve Ronggiang Pasaman Art in the Ujung Gading district, Lembah Melintang sub-district, West Pasaman district.